Iowa fall season data 1999, Paul Hertzel - Hertzel, L. Paulet al (1999)
An annotated list of birds sighted by Paul Hertzel. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1999. Epson - sheet feed